Vitamin D and parental knowledge. (4th April 2011) - Sharma, V; Williams, B; Goddard, A; Coren, M
Abstract : Background: Vitamin D deficiency is common in the paediatric population particularly in inner city areas and severe consequences of this in some patients have been increasingly evident. DOH Guidelines published in January 2010 recommend that children under the age of 5 should receive Vitamin D supplementation. Objective: To assess parental and paediatric healthcare staff's knowledge of Vitamin D, and the need for Vitamin D supplementation in children. Methods: Between March and September 2010, a questionnaire was given to parents of children attending the paediatric out-patient department at St Mary's Hospital. It was also given to paediatric staff who are parents. Results: 116 individuals returned questionnaires; 92 parents of patients (74 mothers, 18 fathers) and 24 healthcare staff (23 female and 1 male). 93 (80%) had children under the age of 5. 22(23%) of the mothers received vitamin D supplement during pregnancy and 14(18%) while breast feeding. 14% were advised to take vitamin D during pregnancy and breast feeding. 9% were offered a blood test for vitamin D levels during pregnancy. 40% of children received vitamin supplements. 24% were advised to give vitamin D to their children. 18% of respondents were unable to cite any dietary or other sources of vitamin D and 39% of respondents were unaware of risk factors for vitamin D deficiency. The majority of respondents were unaware of the government's recommendations for Vitamin D supplementation in children (84% parent's vs 79% healthcare staff) and for mothers during pregnancy and lactation (91% parents vs 88% healthcare staff). Conclusion: Knowledge about Vitamin D was poor in our study population. Both medical staff and parents were unfamiliar with the DOH Guidelines regarding vitamin supplementation in the under 5's. There is an urgent need to educate both clinical staff and parents about Vitamin D and to familiarise both groups with the relevant government advice. There are opportunities to advise about vitamin supplementation during antenatal care and opportunistic child health contacts. We are working with colleagues in midwifery and primary care to address this.